Correlation of Standing Work Position and Musculoskeletal Disorders (MSDs) Complaints on Rack Frame Bending Section Workers in Informal Industry of Rack Making in Surabaya, Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
This research was conducted to analyze the correlation between standing work position and complaints of musculoskeletal disorders on rack frame bending workers in the informal industry of rack making in Surabaya, Indonesia. When doing rack bending, standing work position was affected by work position. The jobs forced workers to work with non-ergonomic standing work position. This caused workers to experience complaints on the skeletal system (MSDs) faster. This research was an observational research with cross sectional design. The sample used a total population of 5 workers. Data obtained by interview, measurement of height and weight and observation of work position. The data analysis method used was descriptive statistics. It was known that due to non-ergonomic standing work position, 40% of rack frame bending workers had a moderate and high MSDs risk category while 20% of other workers were in the low category. In addition, it was known that 40% of workers had low and moderate MSDs complaints category and 20% of other workers had high MSDs complaints category. Based on the results, the standing work position on the rack frame bending workers had a strong and positive correlation with a correlation coefficient of 0.655. In addition to the work position, there was a strong correlation between age, working period, and BMI with MSDs complaints of rack frame bending workers. It was recommended that the employer adjust the frame size on each bending machine and provide seat for workers to rest.
Keywords: standing work position, musculoskeletal disorders complaints, REBA, NBM